Peran Guru Akidah Akhlak dalam Menanamkan Nilai-Nilai Etika Digital - Muchamad Fardan; Muhammad Hamzah; Mohammad Syaifuddin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study examines the role of Akidah Akhlak subject teachers in internalizing digital ethical values ​​amidst the rapid development of information technology. Along with the increasing intensity of social media and digital devices use by students, the need for an understanding of digital ethics is becoming increasingly urgent. This study uses a qualitative approach with a library research method to analyze various relevant literature regarding the contribution of Akidah Akhlak teachers in the formation of students' digital character. The research findings reveal that Akidah Akhlak teachers play an important role in integrating Islamic teachings with the principles of digital ethics. This role includes strengthening the value of honesty in the digital world, responsibility in the use of social media, and the development of digital literacy based on religious values. In addition, this study also identifies a number of strategies that can be implemented by teachers in instilling digital ethics in students, including the use of learning methods that are in accordance with technological advances. The conclusion of this study confirms that the synergy between Akidah Akhlak values ​​and digital ethics has the potential to form a generation that is not only competent in the field of technology, but also has high moral integrity in interacting in the digital space.